Back‐contacted bottom cells with three terminals: Maximizing power extraction from current‐mismatched tandem cells. (6th February 2019) - Rienäcker, Michael; Warren, Emily L.; Schnabel, Manuel; Schulte‐Huxel, Henning; Niepelt, Raphael; Brendel, Rolf; Stradins, Pauls; Tamboli, Adele C.; Peibst, Robby
Abstract: Multi‐junction cells can significantly improve the energy yield of photovoltaic systems over a single‐junction cell. The internal interconnection scheme of the subcells is an important aspect in determining the resulting levelized cost of electricity. For a dual‐junction cell, two approaches are commonly discussed: series‐connected tandem cells with two terminals or independently working subcells in a four‐terminal (4T) tandem device. In this paper, we explore the working principle and the operation modes of a third, rarely discussed option: a three‐terminal (3T) tandem cell using a back‐contacted bottom cell with 3Ts. We use current–voltage measurements of illuminated 3T interdigitated back contact cells and confirm that the front and rear base contacts are at similar quasi‐Fermi level positions, which enables the bottom cell to either efficiently collect surplus carriers, in the case of a current‐limiting or carrier injecting top cell, or inject majority carriers, in the case of a current‐limiting bottom cell. As a result, no current matching is needed. The power output of an idealized 3T bottom cell without resistive effects is independent of the current density applied from the top cell. These characteristics of the 3T bottom cells enable a 3T tandem to operate as efficiently as a 4T tandem, while being compatible with monolithic design and not requiring intermediate grids. We propose a simple equivalent circuit model including additional resistive effects, which describes a real 3T bottom cell and achieves excellent agreement to the experiment. We deduce design guidelines for a 3T bottom cell in different operation regimes. Abstract : We explore the working principle and operation modes of a back‐contacted bottom cell with three terminals (3Ts) for tandem application. Since the third terminal enables efficient collection and injection of majority carriers, current matching in a 3T tandem is superfluous, and the power output of a 3T bottom cell is mostly independent of the current applied from the top cell. A monolithic 3T tandem is predicted to operate as efficiently as a four‐terminal tandem.